Analisis Teori Perkembangan Kognisi Manusia Menurut Jean Piaget - Whildan, Lissya (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2021)
The purpose of this study is to examine further the theory developed by Jean Piaget on the development of human cognition according to the level of thinking at certain stages. The method used in this research is the method of analysis. Sources of data used in this research are books, journals, articles and other scientific works. While the data study technique in this research is literature review (literacy study), and data analysis using content analysis (hemenetic). The result of the research is that the stages of cognitive development according to Jean Piaget are the motor sensory stage (0-2 years), the pre-operational stage (2-7 years), the concrete operational stage (7-12 years), and the formal operational stage (12 years). years and up). In actively understanding the world, children use schema, assimilation, accommodation, organization and equilibration. Children's knowledge is formed gradually in line with the experience of the information they find. According to Piaget, children undergo a definite sequence of stages of cognitive development that point to improvement. Abstrak Tujuan dari penelitian ini adalah untuk mengkaji lebih jauh tentang teori yang dikembangkan oleh Jean Piaget terhadap perkembangan kognisi manusia sesuai tingkat berfikir pada tahapan-tahapan usia tertentu. Metode yang digunakan dalam penelitian ini adalah metode analisis. Sumber data yang digunakan dalam penelitian ini yaitu buku, jurnal, artikel, dan karya ilmiah lainnya. Sedangkan teknik pengumpulan data pada penelitian ini adalah kajian pustaka (studi literasi), dan nalisis data menggunakan analisis isi (hemenetik). Hasil penelitian ini adalah bahwa tahapan-tahapan perkembangan kognisi menurut Jean Piaget yaitu tahap sensory motorik (0-2 tahun), tahap pra-operasional (2-7 tahun), tahap operasional konkret (7-12 tahun), dan operasional formal (12 tahun ke atas). Dalam memahami dunia secara aktif, anak menggunakan skema, asimilasi, akomodasi, organisasi dan equilibrasi. Pengetahuan anak terbentuk secara berangsur sejalan dengan pengalaman tentang informasi-informasi yang ditemui. Menurut Piaget, anak menjalani urutan yang sudah pasti dari tahap-tahap perkembangan kognitif yang menujukan peningkatan.